2014
DOI: 10.1039/c4cp03106g
|View full text |Cite
|
Sign up to set email alerts
|

A partial differential equation for pseudocontact shift

Abstract: It is demonstrated that pseudocontact shift (PCS), viewed as a scalar or a tensor field in three dimensions, obeys an elliptic partial differential equation with a source term that depends on the Hessian of the unpaired electron probability density. The equation enables straightforward PCS prediction and analysis in systems with delocalized unpaired electrons, particularly for the nuclei located in their immediate vicinity. It is also shown that the probability density of the unpaired electron may be extracted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…If the paramagnetic centre is distributed with some probability density ρ ( r ), the convolution of this density with eqn (1) obeys 21 the partial differential equation that we have recently derived: 20 where ∇ is the gradient operator, H ρ ( r ) is the Hessian of ρ ( r ) and the denominator is to be understood as the inverse Laplacian. The best way to solve this equation is to use fast Fourier transforms: 21 …”
Section: Extracting Spin Label Distributions From Pcs Datamentioning
confidence: 99%
See 2 more Smart Citations
“…If the paramagnetic centre is distributed with some probability density ρ ( r ), the convolution of this density with eqn (1) obeys 21 the partial differential equation that we have recently derived: 20 where ∇ is the gradient operator, H ρ ( r ) is the Hessian of ρ ( r ) and the denominator is to be understood as the inverse Laplacian. The best way to solve this equation is to use fast Fourier transforms: 21 …”
Section: Extracting Spin Label Distributions From Pcs Datamentioning
confidence: 99%
“…20 We demonstrate here that it may be used to recover the spin label position distribution from the experimental PCS data. This creates a new window into protein structure and dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important source of experimental information concerning the structure of the metal sites in proteins is EXAFS spectroscopy [60,61]. As mentioned above, it is known from EXAFS studies that the PI has a Cu-Cu distance of ~3.4 Å [35] and that the NI has at least two Cu-Cu distances of 3.3 Å [15].…”
Section: A Comparison With the Exafs Spectra: A Combined Qm/mm/exafs mentioning
confidence: 99%
“…Considering that the overall accuracy of the EXAFS geometries (~0.01 Å [60,61]) is better than that of QM calculations (~0.05 Å [69,70]), w EXAFS is normally increased until the geometry reaches a state when χ 2 does not change. Calibration studies showed that this EXAFS/QM approach worked excellently and actually could improve the EXAFS structures of small inorganic complexes (i.e.…”
mentioning
confidence: 99%